Meta‐analysis of natural, unnatural and cause‐specific mortality rates following discharge from in‐patient psychiatric facilities. (10th August 2019) - Swaraj, S.; Wang, M.; Chung, D.; Curtis, J.; Firth, J.; Ramanuj, P. P.; Sara, G.; Large, M.
Abstract : Background: People discharged from in‐patient psychiatric facilities have highly elevated rates of suicide, and there is increasing concern about natural mortality among the seriously mentally ill. Method: A meta‐analysis of English‐language, peer‐reviewed longitudinal studies of mortality among patients discharged from in‐patient psychiatric facilities was conducted using papers published in MEDLINE, PsycINFO or EMBASE (from 1 January 1960 to 1 April 2018) located using the terms ((suicid*).ti AND (hospital OR discharg* OR inpatient OR in‐patient OR admit*)).ab and ((mortality OR outcome* OR death*) AND (psych* OR mental*)).ti AND (admit* OR admis* OR hospital* OR inpatient* OR in‐patient* OR discharg*).ab. Pooled mortality rates for aggregated natural and unnatural causes, and the specific causes of suicide, accident, homicide, vascular, neoplastic, respiratory, gastrointestinal, infectious and metabolic death were calculated using a random‐effects meta‐analytic model. Between‐study heterogeneity was investigated using subgroup analysis and metaregression. Results: The pooled natural death rate of 1128 per 100 000 person‐years exceeded the pooled unnatural deaths of 479 per 100 000 person‐year among studies with varying periods of follow‐up. Natural deaths significantly exceeded unnatural deaths among studies with a mean follow‐up of longer than 2 years, and vascular deaths exceeded suicide deaths among studies with mean period of follow‐up of 5 years or longer. Conclusion: Suicide may be the largest single cause of death in the short term after discharge from in‐patient psychiatric facilities but vascular disease is the major cause of mortality in the medium‐ and long‐term.